Flow channel selectivity control material as well as preparation method and application thereof

By using flow channel selective control materials prepared by nano-based cores and other materials during fracturing of natural gas wells, selective control of gas and water is achieved, solving the problem of water production in the same layer of gas and water after fracturing of gas wells, and improving production capacity and water control effect.

CN119912651APending Publication Date: 2025-05-02CNPC BOHAI DRILLING ENG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311427427.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

After the natural gas well fracturing, the gas and water production in the same layer is severe, resulting in a decline in production capacity. The existing water control system cannot achieve selective gas and water control, and the construction risk is high and the effect is short-lived.

Method used

The flow channel selective control material is used, which consists of nano-based cores, coupling agents, initiators and regulators. It is formed by high-speed mechanical stirring and radical polymerization. It can self-coalize at high temperatures and high mineralization of the formation, blocking the water-producing channel without affecting the gas-producing channel.

Benefits of technology

It realizes selective gas-water control during gas well fracturing, can effectively seal the water production channel, improve injection and sealing properties, and extend the water control effect, and is suitable for low-permeability reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912651A_ABST
    Figure CN119912651A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield chemistry, in particular to a flow channel selectivity control material and a preparation method and application thereof, and the flow channel selectivity control material is prepared from a nano-based core, a coupling agent, an initiator and a regulating agent according to the weight ratio of 1: (5-10): (0.8-1.2): (5-10). The flow channel selectivity control material has the advantages of being wide in raw material source, low in cost and simple in process, a flow channel selectivity control system made of the flow channel selectivity control material is used, spontaneous percolation and deep migration into a low-permeability reservoir matrix in the gas well fracturing process can be achieved, and the flow channel selectivity control material is suitable for gas well fracturing. The coalescence behavior occurs under the stratum condition, the particle size of the system is changed from the nanometer scale to the micrometer scale, and a water production channel under the condition of the same layer of gas and water is effectively blocked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a flow channel selectivity control material, a preparation method thereof and an application thereof. Background Art

[0002] Natural gas wells generally have problems such as poor reservoir properties, low permeability, and insufficient capacity construction, so most of them use fracturing technology to transform the reservoir. For the top and bottom aquifers of the gas reservoir, the water production characteristics are relatively clear, and fracturing can be achieved by inserting a packer to avoid the water-producing layer. For the gas-water coexistence layer, the water content relationship is more complex and difficult to accurately identify, which often causes water production after fracturing, seriously affecting the gas well production capacity. Non-selective water control systems such as polymer gels and inorganic granular materials have high plugging strength, but cannot achieve gas-water selective plugging, and the construction risk is relatively high. Conventional selective water control systems such as foams are easily affected by reservoir conditions, have poor injectability and a short effective period of action, and are difficult to meet the long-term water control needs of gas wells.

[0003] CN115572589A discloses a gas well plugging agent formula and its preparation method, which is mainly composed of water-swelling material and surfactant, and achieves the purpose of plugging aquifers by underground water-swelling of the material, but the material is produced by granulation, and the particle size distribution is 0.2-0.5mm, which cannot achieve effective injection and plugging of low-permeability reservoirs with smaller pore throats of gas wells. CN109824302B discloses a plugging composition, a plugging agent and its preparation method, which is mainly composed of oil well cement, silicon powder and additives, has high plugging strength and corrosion resistance, and is suitable for plugging water in high-sulfur gas fields, but the system does not have gas-water selectivity, and can only achieve general chemical plugging. The water production problem of gas and water in the same layer cannot be effectively solved, and there is a great threat to the gas well production capacity. Summary of the invention

[0004] In view of the technical difficulties of serious water production in the same layer of gas and water and rapid decline in production capacity after fracturing of a natural gas well, the present invention provides a flow channel selective control material, a preparation method and application thereof. The flow channel selective control system prepared using the flow channel selective control material in the present invention can enter the formation together with the fracturing fluid, and under the influence of the high temperature and high mineralization of the formation, particles agglomerate in the water phase, blocking the water production channel without affecting the gas production channel, thereby achieving the purpose of gas-water selective control.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] In the first aspect, the present invention provides a flow channel selectivity control material, wherein the raw materials for preparing the flow channel selectivity control material include a nano-based core, a coupling agent, an initiator and a regulator;

[0007] The weight ratio of the nano-based core, coupling agent, initiator and regulator is 1: (5-10): (0.8-1.2): (5-10).

[0008] Furthermore,

[0009] The nano-based core is any one of nano-silicon dioxide, nano-graphene oxide and nano-molybdenum disulfide or a combination thereof.

[0010] Furthermore,

[0011] The particle size of the nano-core is 50-200nm.

[0012] Furthermore,

[0013] The coupling agent is any one of vinyl trimethoxy silane, vinyl tri (2-methoxyethoxy) silane and vinyl tributylidene oxime silane or a combination thereof.

[0014] Furthermore,

[0015] The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate or a combination thereof.

[0016] Furthermore,

[0017] The regulating agent is any one of sodium styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid and 2-acrylamide dodecane sulfonic acid or a combination thereof.

[0018] In a second aspect, the present invention provides a method for preparing the flow channel selectivity control material, comprising the following steps:

[0019] Step (1): adding the nano-core into deionized water and forming a uniform dispersion by high-speed mechanical stirring;

[0020] Step (2): adding a coupling agent to the dispersion of step (1), raising the temperature, and stirring at a low speed to react;

[0021] Step (3): adding an initiator and a regulator to the solution after the reaction in step (2) to initiate a free radical polymerization reaction. The reaction conditions are the same as those in step (2), and nitrogen is continuously introduced for protection to carry out the reaction.

[0022] Step (4): filtering the solution obtained in step (3) to remove unreacted substances and obtain filtered solids;

[0023] Step (5): Dry the solid filtered out in step (4) to obtain a flow channel selectivity control material.

[0024] Furthermore,

[0025] The concentration of the nano-core in deionized water in step (1) is 1-5%, and the stirring rate of the high-speed mechanical stirring is 1000-10000 rpm;

[0026] The reaction temperature in step (2) is 40-60° C., the stirring rate of the low-speed stirring is 100-500 rpm, and the reaction time is 12-48 h;

[0027] The reaction time in step (3) is 12 to 48 hours;

[0028] The filtration method in step (4) is any one of ordinary filtration, vacuum filtration and positive pressure filtration or a combination thereof, and the filter membrane used in the filtration process is a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm.

[0029] In a third aspect, the application of the flow channel selectivity control material provided by the present invention is to mix the flow channel selectivity control material with liquid preparation water to prepare a flow channel selectivity control system, and the flow channel selectivity control system is used to block the water production channel without affecting the gas production channel during the gas well fracturing process;

[0030] The components of the flow channel selectivity control system are as follows:

[0031] A flow channel selectivity control material and water for liquid preparation, wherein the weight ratio of the flow channel selectivity control material to water is (1-5): (95-99);

[0032] The water used for the preparation of the solution is deionized water or clean water.

[0033] Furthermore,

[0034] The preparation method of the flow channel selectivity control system comprises the following steps:

[0035] Step (1): dispersing the flow channel selectivity control material in the liquid preparation water under low speed stirring conditions to form a uniform dispersion;

[0036] Step (2): allowing the dispersion in step (1) to stand and taking the supernatant for use;

[0037] Wherein, the stirring rate of the low-speed stirring in step (1) is 100 to 500 rpm;

[0038] The standing time in step (2) is 12 to 48 hours.

[0039] Based on the above technical solutions, the technical effects that can be achieved by the present invention are:

[0040] The nano-based core of the flow channel selective control material of the present invention has the advantages of wide raw material sources and low cost, simple coupling process technology and strong operability, and the grafted sulfonic acid group has good hydrophilicity, ensuring that the system has the characteristics of easy injection of nano-particle size, uniform dispersion and strong hydrophilicity. The flow channel selective control system made of the flow channel selective control material can realize spontaneous infiltration and deep migration into the low-permeability reservoir matrix during gas well fracturing. Under the dual influence of temperature and mineralization under formation conditions, self-aggregation behavior occurs in the water phase, and the system particle size changes from nanometer scale to micrometer scale, which effectively blocks the water production channel under gas-water co-layer conditions.

[0041] The flow channel selective control system during the gas well fracturing process of the present invention can be used as a specific segment plug in the gas well fracturing process or a water plugging construction agent for high-water-content gas wells. It has good injectability and plugging properties in low-permeability reservoirs, can achieve efficient regulation of water-producing channels, and has reference significance for the advanced management of water-producing gas wells. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 The macroscopic morphology of the flow channel selectivity control material prepared in Example 1 of the present invention;

[0044] Figure 2 The macroscopic morphology of the flow channel selectivity control system prepared in Example 7 of the present invention before and after aging under simulated reservoir conditions. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0046] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0048] A method for evaluating a flow channel selectivity control system, the method comprising the following steps:

[0049] (1) aging the supernatant of the flow channel selectivity control system at simulated reservoir temperature and salinity;

[0050] (2) Take out regularly to observe the macroscopic morphology of the flow channel selectivity control system and test the particle size change.

[0051] The simulated reservoir temperature in step (1) is 100-130°C; the mineralization is 5×10 3 ~20×10 4 mg / L; the regular removal time interval in step (2) is 1 to 30 days; the particle size testing instrument is any one of a laser particle size analyzer, an optical microscope and a scanning electron microscope or a combination thereof.

[0052] Example 1

[0053] This embodiment is to illustrate a method for preparing a flow channel selectivity control material of the present invention, and the specific steps are as follows:

[0054] (1) adding 1% nano-silica into 100 mL of deionized water and stirring at 10,000 rpm to form a uniform dispersion;

[0055] (2) adding 5.0 g of vinyltrimethoxysilane to the dispersion of step (1), heating to 50° C., and stirring at a low speed of 100 rpm for 24 h;

[0056] (3) adding 0.8 g potassium persulfate and 5.0 g sodium styrene sulfonate to the solution after the reaction in step (2) to initiate a free radical polymerization reaction. The reaction conditions were the same as those in step (2), and nitrogen was continuously introduced for protection. The reaction was continued for 24 h.

[0057] (4) vacuum filtering the solution obtained in step (3) to remove unreacted substances and obtain filtered solids;

[0058] (5) freeze-drying the solid filtered out in step (4) to obtain a flow channel selectivity control material.

[0059] The macroscopic morphology of a flow channel selectivity control material obtained in this embodiment is as follows Figure 1 As shown, it is a white powdery solid.

[0060] Example 2

[0061] This embodiment is to illustrate a method for preparing a flow channel selectivity control material of the present invention, and the specific steps are as follows:

[0062] (1) adding 1.5% by mass of nano-graphene oxide into 100 mL of deionized water and stirring at 8000 rpm to form a uniform dispersion;

[0063] (2) adding 5.0 g of vinyl tris(2-methoxyethoxy)silane to the dispersion of step (1), heating to 60° C., and stirring at a low speed of 200 rpm for reaction for 24 h;

[0064] (3) adding 1.0 g of ammonium persulfate and 6.0 g of 2-acrylamide-2-methylpropanesulfonic acid to the solution after the reaction in step (2) to initiate a free radical polymerization reaction. The reaction conditions were the same as those in step (2), and nitrogen was continuously introduced for protection. The reaction was continued for 24 h.

[0065] (4) filtering the solution obtained in step (3) under positive pressure to remove unreacted substances and obtain filtered solids;

[0066] (5) freeze-drying the solid filtered out in step (4) to obtain a flow channel selectivity control material.

[0067] Example 3

[0068] This embodiment is to illustrate a method for preparing a flow channel selectivity control material of the present invention, and the specific steps are as follows:

[0069] (1) Add 2% by mass of nano-molybdenum disulfide into 100 mL of deionized water and stir at 8000 rpm to form a uniform dispersion;

[0070] (2) adding 7.0 g of vinyltributylidene oxime silane to the dispersion of step (1), heating to 60° C., and stirring at a low speed of 150 rpm for 30 h;

[0071] (3) adding 1.0 g of sodium persulfate and 10.0 g of 2-acrylamidododecanesulfonic acid to the solution after the reaction in step (2) to initiate a free radical polymerization reaction. The reaction conditions were the same as those in step (2), and nitrogen was continuously introduced for protection. The reaction was continued for 30 h.

[0072] (4) filtering the solution obtained in step (3) under positive pressure to remove unreacted substances and obtain filtered solids;

[0073] (5) freeze-drying the solid filtered out in step (4) to obtain a flow channel selectivity control material.

[0074] Example 4

[0075] This embodiment is to illustrate a method for preparing a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0076] (1) Under low-speed stirring conditions of 100 rpm, the flow channel selectivity control material prepared in Example 1 was dispersed in clean water at a concentration of 1% by mass to form a uniform dispersion;

[0077] (2) The dispersion in step (1) was allowed to stand for 24 hours and the supernatant was taken for use.

[0078] Example 5

[0079] This embodiment is to illustrate a method for preparing a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0080] (1) Under low-speed stirring conditions of 200 rpm, the flow channel selectivity control material prepared in Example 2 was dispersed in clean water at a concentration of 1.5% by mass to form a uniform dispersion;

[0081] (2) The dispersion in step (1) was allowed to stand for 24 hours and the supernatant was taken for use.

[0082] Example 6

[0083] This embodiment is to illustrate a method for preparing a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0084] (1) Under low-speed stirring conditions of 200 rpm, the flow channel selectivity control material prepared in Example 3 was dispersed in clean water at a concentration of 2% by mass to form a uniform dispersion;

[0085] (2) The dispersion in step (1) was allowed to stand for 24 hours and the supernatant was taken for use.

[0086] Example 7

[0087] This embodiment is intended to illustrate a method for evaluating a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0088] (1) A certain amount of salt was added to the flow channel selectivity control system prepared in Example 4 and stirred evenly to obtain a mineralization degree of 1×10 4 mg / L solution, and age the solution at 130°C;

[0089] (2) Take out the samples regularly and test the particle size changes using a laser particle size analyzer.

[0090] The particle size variation of a flow channel selectivity control system obtained in this example is shown in Table 1.

[0091] Table 1 Changes in particle size of the system after aging under simulated reservoir conditions

[0092] The macroscopic morphology of a flow channel selectivity control system obtained in this embodiment before and after aging under simulated reservoir conditions is as follows: Figure 2 As shown in the figure, the solution on the left is before aging, and the solution on the right is after aging. As can be seen from the figure, the solution before aging is clear and transparent, and after aging, obvious particles agglomerate in the lower part of the solution, thus effectively blocking the water production channel.

[0093] Example 8

[0094] This embodiment is intended to illustrate a method for evaluating a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0095] (1) A certain amount of salt was added to the flow channel selectivity control system prepared in Example 5 and stirred evenly to obtain a mineralization degree of 10×10 4 mg / L solution, and age the solution at 110°C;

[0096] (2) Take out the samples regularly and test the particle size changes using an optical microscope.

[0097] The particle size variation of a flow channel selectivity control system obtained in this example is shown in Table 2.

[0098] Table 2 Changes in particle size of the system after aging under simulated reservoir conditions

[0099] Example 9

[0100] This embodiment is intended to illustrate a method for evaluating a flow channel selectivity control system of the present invention, and the specific steps are as follows:

[0101] (1) A certain amount of salt was added to the flow channel selectivity control system prepared in Example 6 and stirred evenly to obtain a mineralization degree of 20×10 4 mg / L solution, and age the solution at 100°C;

[0102] (2) Take out the samples regularly and test the particle size change using a scanning electron microscope.

[0103] The particle size variation of a flow channel selectivity control system obtained in this example is shown in Table 3.

[0104] Table 3 Changes in particle size of the system after aging under simulated reservoir conditions

[0105] Comparative Example 1

[0106] The method of Example 7 is different in that in step (1), the flow channel selectivity control material used in the flow channel selectivity control system is unmodified nano-silicon dioxide. The test conditions are the same as those of Example 7, and the test results are shown in Table 4.

[0107] Table 4 Changes in particle size of the system after aging under simulated reservoir conditions

[0108] According to the results shown in Table 4, the flow channel selectivity control system prepared by using unmodified nano-silica as the flow channel selectivity control material quickly self-aggregates under high temperature and low salt conditions and cannot migrate to deep formations, making it difficult to achieve the effect of flow channel selectivity control.

[0109] Comparative Example 2

[0110] The method of Example 8 is different in that in step (1), the flow channel selectivity control material used in the flow channel selectivity control system is unmodified nano graphene oxide. The test conditions are the same as those of Example 8, and the test results are shown in Table 5.

[0111] Table 5 Particle size changes of the system after aging under simulated reservoir conditions

[0112] According to the results shown in Table 5, the flow channel selectivity control system prepared by using unmodified nano-graphene oxide as the flow channel selectivity control material quickly self-aggregates under high temperature and high salt conditions, cannot migrate to deep formations, and it is difficult to achieve the effect of flow channel selectivity control.

[0113] Comparative Example 3

[0114] The method of Example 9 is different in that in step (1), the flow channel selectivity control material used in the flow channel selectivity control system is unmodified nano-molybdenum disulfide. The test conditions are the same as those of Example 9, and the test results are shown in Table 6.

[0115] Table 6 Changes in particle size of the system after aging under simulated reservoir conditions

[0116] According to the results shown in Table 6, the flow channel selectivity control system prepared using unmodified nano-silica as the flow channel selectivity control material quickly self-aggregates under high temperature and high salt conditions and cannot migrate to deep formations, making it difficult to achieve the effect of flow channel selectivity control.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flow channel selectivity control material, characterized in that: The raw materials for preparing the flow channel selectivity control material include nano-based core, coupling agent, initiator and regulator; The weight ratio of the nano-based core, coupling agent, initiator and regulator is 1: (5-10): (0.8-1.2): (5-10).

2. The flow channel selectivity control material according to claim 1, characterized in that: The nano-based core is any one of nano-silicon dioxide, nano-graphene oxide and nano-molybdenum disulfide or a combination thereof.

3. The flow channel selectivity control material according to claim 1, characterized in that: The particle size of the nano-core is 50-200nm.

4. The flow channel selectivity control material according to claim 1, characterized in that: The coupling agent is any one of vinyl trimethoxy silane, vinyl tri (2-methoxyethoxy) silane and vinyl tributylidene oxime silane or a combination thereof.

5. The flow channel selectivity control material according to claim 1, characterized in that: The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate or a combination thereof.

6. The flow channel selectivity control material according to claim 1, characterized in that: The regulating agent is any one of sodium styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid and 2-acrylamide dodecane sulfonic acid or a combination thereof.

7. A method for preparing a flow channel selectivity control material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): adding the nano-core into deionized water and forming a uniform dispersion by high-speed mechanical stirring; Step (2): adding a coupling agent to the dispersion of step (1), raising the temperature, and stirring at a low speed to react; Step (3): adding an initiator and a regulator to the solution after the reaction in step (2) to initiate a free radical polymerization reaction. The reaction conditions are the same as those in step (2), and nitrogen is continuously introduced for protection to carry out the reaction. Step (4): filtering the solution obtained in step (3) to remove unreacted substances and obtain filtered solids; Step (5): Dry the solid filtered out in step (4) to obtain a flow channel selectivity control material.

8. The preparation method according to claim 7, characterized in that: The concentration of the nano-core in deionized water in step (1) is 1-5%, and the stirring rate of the high-speed mechanical stirring is 1000-10000 rpm; The reaction temperature in step (2) is 40-60° C., the stirring rate of the low-speed stirring is 100-500 rpm, and the reaction time is 12-48 h; The reaction time in step (3) is 12 to 48 hours; The filtration method in step (4) is any one of ordinary filtration, vacuum filtration and positive pressure filtration or a combination thereof, and the filter membrane used in the filtration process is a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm.

9. An application of the flow channel selectivity control material according to any one of claims 1 to 6, characterized in that: The flow channel selectivity control material is mixed with the liquid preparation water to prepare a flow channel selectivity control system, and the flow channel selectivity control system is used to block the water production channel without affecting the gas production channel during the gas well fracturing process; The components of the flow channel selectivity control system are as follows: A flow channel selectivity control material and water for liquid preparation, wherein the weight ratio of the flow channel selectivity control material to water is (1-5): (95-99); The water used for the preparation of the solution is deionized water or clean water.

10. The use according to claim 9, characterized in that: The preparation method of the flow channel selectivity control system comprises the following steps: Step (1): dispersing the flow channel selectivity control material in the liquid preparation water under low speed stirring conditions to form a uniform dispersion; Step (2): allowing the dispersion in step (1) to stand and taking the supernatant for use; Wherein, the stirring rate of the low-speed stirring described in step (1) is 100 to 500 rpm; The standing time in step (2) is 12 to 48 hours.